QUALITY OF FISH OIL EXTRACTED FROM BARRAMUNDI BY - PRODUCT BY ENZYMATIC HYDROLYSIS METHOD (Vietnam Journal of Agriculture and Environment, 2023)
Study on the fish oil extraction from barramundi by - product by enzymatic hydrolysis method was carried out. The parameters of hydrolysis process, oil recovery and chemical quality including free fatty acid content, acid value, peroxide value, iodine value and saponification value of fish oil were determined. The study results showed that a considerable amount of oil can be extracted from barramundi by - product. The optimal parameters of enzymatic hydrolysis process for recovering the fish oil were the water/material ratio of 50%, enzyme/material ratio of 0.3%, hydrolysis temperature of 600C and hydrolysis time of 2 hours. The fish oil obtained from hydrolysis of barramundi by - product in optimum conditions was rich in omega-3 fatty acids, especially docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). The major fatty acids in barramundi by - product oil were palmitic acid, oleic acid and docosahexaenoic acid. This study suggested that the barramundi by - product generated from fish processing industry can be utilized as a good source for fish oil recovery. Barramundi by - product oil can be used in aquaculture feed or considered as a valuable source for human consumption.